2018
DOI: 10.3390/molecules23061403
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Potency of Flavonoids on Mushroom Tyrosinase Inhibitory Activity and Melanin Synthesis in Melanocytes

Abstract: Twenty-seven flavonoids isolated from Dalbergia parviflora with vast structural diversity were screened for inhibitory activity against mushroom and murine tyrosinases using l-DOPA as the substrate. Among the flavonoids tested, only four—khrinone (5), cajanin (9), (3RS)-3′-hydroxy-8-methoxy vestitol (21), and (6aR,11aR)-3,8-dihydroxy-9-methoxy pterocarpan (27)—reacted with mushroom tyrosinase, with IC50 values of 54.0, 67.9, 67.8, and 16.7 μM, respectively, and only compound 27 showed inhibitory activity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 31 publications
2
43
0
1
Order By: Relevance
“…A pterocarpan (IC50 = 16.7 μM) and some isoflavones and isoflavans isolated from Dalbergia parviflora (Figure 11) have been also recently reported as inhibitors of the diphenolase activity of mushroom tyrosinase [95]. A series of flavonoids derivatives from the root bark of Broussonetia papyrifera, first of all broussoflavonol J (IC 50 = 9.29 µM), have been found to be more active than kojic acid as inhibitors of the monophenolase acitivty of the enzyme [92] (Figure 11).…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 81%
See 3 more Smart Citations
“…A pterocarpan (IC50 = 16.7 μM) and some isoflavones and isoflavans isolated from Dalbergia parviflora (Figure 11) have been also recently reported as inhibitors of the diphenolase activity of mushroom tyrosinase [95]. A series of flavonoids derivatives from the root bark of Broussonetia papyrifera, first of all broussoflavonol J (IC 50 = 9.29 µM), have been found to be more active than kojic acid as inhibitors of the monophenolase acitivty of the enzyme [92] (Figure 11).…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 81%
“…Very potent (IC50 values in the range 0.10-7.5 μM) mushroom tyrosinase inhibitors have been isolated from licorice (Figure 12), the most active belonging to the isoflavan class [108][109][110]. A pterocarpan (IC 50 = 16.7 µM) and some isoflavones and isoflavans isolated from Dalbergia parviflora ( Figure 11) have been also recently reported as inhibitors of the diphenolase activity of mushroom tyrosinase [95].…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 87%
See 2 more Smart Citations
“…Arung et al [23] reported that a prenylated flavonoid from the wood of Artocarpus heterophyllus had good activity against melanin synthesis through a reduction in tyrosinase activity. Worrawat et al [24] isolated flavonoids from Dalbergia parviflora and showed that the flavonoids had inhibitory activity against murine tyrosinases and effectively inhibited melanin formation in B16 melanoma cells without being significantly toxic to the cells. These reports collectively suggest that SIFs extract could have good inhibitory activity against tyrosinase.…”
Section: The Effect Of Sifs Extract On A375 Cell Activitymentioning
confidence: 99%